A legal geography of property, tenure, exclusion, and rights in Cambodia: exposing an incongruous property narrative for non‐Western settings. (28th November 2014) - Gillespie, Josephine
Abstract: The scholarship of legal geography provides an alternative way of conceptualising human–environmental relationships. While laws determine access to and regulate use of land through practices of bounding and excluding, geographical studies provide insights into the way that both physical and social processes create places. The meeting of these perspectives is invaluable. Legal geography perspectives are coming of age in an era when transdisciplinary perspectives on human/nonhuman–landscape interactions are of core concern to wider land use policy considerations. This paper draws on legal geography scholarship about property framed around three key concepts (1) tenure security, (2) exclusion, and (3) rights to reveal the social complexity surrounding these issues. This complexity is magnified in non‐Western settings, and in this paper, the legal geography perspective of analysis is extended to a developing country context. Using Cambodia as the primary setting, this paper challenges the unquestioning exportation of a dominant 'Western' property model into non‐Western contexts.